Lanthanide‐Doped Core@Multishell Nanoarchitectures: Multimodal Excitable Upconverting/Downshifting Luminescence and High‐Level Anti‐Counterfeiting. Issue 19 (20th April 2020) - Huang, Hai; Chen, Jiangkun; Liu, Yutong; Lin, Jidong; Wang, Shaoxiong; Huang, Feng; Chen, Daqin
Abstract: The development of luminescent materials with concurrent multimodal emissions is a great challenge to improve security and data storage density. Lanthanide‐doped nanocrystals are particularly appropriate for such applications for their abundant intermediate energy states and distinguishable spectroscopic profiles. However, traditional lanthanide luminescent nanoparticles have a limited capacity for information storage or complexity to shield against counterfeiting. Herein, it is demonstrated that the combination of upconverting and downshifting emissions in a particulate designed lanthanide‐doped core@multishell nanoarchitecture allows the generation of multicolor dual‐modal luminescence over a wide spectral range for complex information storage. Precise control of lanthanide dopants distribution in the core and distinct shells enables simultaneous excitation of 980/808 nm focusing/defocusing laser and 254 nm light and produces complex upconverting emissions from Er, Tm, Eu, and Tb via multiphoton energy transfer processes and downshifting emissions from Eu and Tb via efficient energy transfer from Ce to Eu/Tb in Gd‐assisted lattices. It is experimentally proven that multiple visualized anti‐counterfeit and information encryption with facile decryption and authentication using screen‐printing inks containing the present core@multishell nanocrystals are practically applicable by selecting different excitation modes. Abstract : Lanthanide‐doped core@multishell nanoarchitectures are constructed and precise control over dopants distribution in the distinct layers enables diversified excitations from the combination of UV light and near‐infrared (NIR) focusing/defocusing laser, leading to complex upconverting/downshifting combined luminescence in a wide spectral region. Multiple visualized anticounterfeit and information encryption/decryption using screen‐printing inks containing the developed nanocrystals are demonstrated to be practically applicable through appropriately selecting excitation modes.